Ca2+/Calmodulin-NOS/NO-TNFs Pathway Hallmarks the Inflammation Response of Oyster During Aerial Exposure - Chen, Hao; Xin, Lusheng; Wang, Lin; Zhang, Huan; Liu, Rui; Wang, Hao; Qiao, Xue; Wang, Lingling; Song, Linsheng (Frontiers in Marine Science, 2021)
Aerial exposure (emersion) due to the periodical ebb and flow of tides is a major stressor for intertidal organisms and a key environmental factor in shaping their local communities. Oysters are among the most emersion-tolerant mollusc species and can survive for several days under aerial exposure. Noticeably, overwhelming inflammation responses could occur during the emersion stress. However, mechanisms beneath the activation and modulation of emersion-induced inflammation response have remained largely unknown. Ca2+ is an important intracellular second messenger that plays indispensable roles in inflammation response by cooperation with calmodulin genes. Here, we showed that intracellular Ca2+ accumulates rapidly in oyster haemocytes during emersion stress along with the changes in the protein levels of three calmodulin genes, which function as intracellular sensors of Ca2+. As downstream effector of Ca2+/calmodulin complex, nitrite oxide synthase (NOS) activity in haemocytes was enhanced during the emersion stress, facilitating a greater production of nitrite oxide (NO). Augmentation of nitrite oxide concentration was associated with the increased mRNA expression levels of two oyster cytokines (CgTNFs) during aerial exposure. The robust accumulation of cytokines and severe injury of tissues in oysters have been regarded as potential cause and marker of their death in prolonged emersion stress. Here, both the expression levels of CgTNFs and the tissue injuries of oysters were attenuated when Ca2+/calmodulin complex or NOS activity were repressed in vivo during the emersion stress. These findings indicate that Ca2+/calmodulin-NOS/NO-CgTNFs pathway is critically involved in the emersion-induced inflammation response in oysters and plays a role in the resistance against long-term aerial exposure.